2013
DOI: 10.1002/14651858.cd001049.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol for acute traumatic brain injury

Abstract: Cochrane Database of Systematic Reviews Analysis 1.2. Comparison 1 ICP-directed mannitol ('treatment') compared to mannitol according to neurological signs ('control'), Outcome 2 Death or severe disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…The efficacy of existing neuroprotective treatments for high ICP after TBI remains uncertain. There is insufficient data supporting pre-hospital administration of mannitol for treatment of high ICP after TBI [28]. Mass lesions and an increase in brain water content (edema) and cerebral blood volume contribute to raised ICP in TBI [29].…”
Section: Current Status Of Treatments For Tbimentioning
confidence: 99%
“…The efficacy of existing neuroprotective treatments for high ICP after TBI remains uncertain. There is insufficient data supporting pre-hospital administration of mannitol for treatment of high ICP after TBI [28]. Mass lesions and an increase in brain water content (edema) and cerebral blood volume contribute to raised ICP in TBI [29].…”
Section: Current Status Of Treatments For Tbimentioning
confidence: 99%
“…While mannitol has been widely adopted in the hospital setting, there are no data supporting its effectiveness in the prehospital setting (Sayre et al, 1996;Wakai et al, 2013) and it may actually be harmful in pediatric patients (White et al, 2001). The classic hyperosmolar fluid used in the empiric treatment of cerebral herniation is mannitol.…”
Section: Brain-directed Hyperosmolar Fluid Therapymentioning
confidence: 99%
“…A recent Cochrane Review concluded that mannitol has a beneficial effect on mortality after TBI when compared to pentobarbital treatment but may have a detrimental effect on mortality when compared to HTS. 64 There are differences in the results from various studies on the duration of ICP reduction, as well as on the improvement in brain oxygenation with HTS. These differences may be related to the concentration of HTS used.…”
Section: Shortcomingsmentioning
confidence: 99%